PENGUNGKAPAN SYARIAH PADA BANK SYARIAH DI INDONESIA - Nizar Krisna Ardian; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2015)
This study aims to examine the disclosure of sharia Islamic banks in Indonesia. With the independent variable is the size of the supervisory board of sharia, cross membership of the sharia supervisory board, sharia supervisory board member with expertise in accounting, banking, economics, and finance on the disclosure of zakat, the disclosure report of the supervisory board of sharia and sharia supervisory board disclosures in the annual reports of Islamic banks.The population in this study is the entire Islamic banks in Indonesia in 2011, 2012, and 2013. The number of banks research sample totaled 33. In order to obtain research data for 33 samples of data. The analysis technique used is a multiple regression analysis.The analysis showed that the disclosure of zakat is significantly affected by the size of the sharia supervisory board, cross memberships of the sharia supervisory board, and sharia supervisory board expertise in accounting / economics / banking / finance. Disclosure of Shariah supervisory board report significantly influenced by sharia supervisory board expertise in accounting / economics/ banking/ finance. While disclosure of sharia supervisory board significantly influenced by cross- membership of sharia supervisory board